환경정책이 축산업의 규모와 입지에 미친 파급효과 -축산농가 규모별 분석 - 박두호; Park, Dooho (자원·환경경제연구, 2006)
This paper explores the relatilonship between state level environmental regulations and stocking and location decisions in the U.S livestock and poultry industry (beef, chicken, dairy and hogs), Rather than conduct this analysis on a species by species basis, the overall size of the livestock industry(expressed in animal units) and the size of Industry found on large, medium and small operations by state (48) and over time (29 years), which is panel data analysis, Generally, regulations seem to be induced by the structural change of industry; when industry creates externalities, regulators try to address them with policy tools to internalize them, Written regulatory stringency may not effect behavioral change; rather the state's willingness to enforce regulations seems to have a measurable influence. However, in the presence of rapid structural change, industry location is affected by written regulatory stringency. Policy enforcement activity was shown to influence inventory decisions in general and larger operations were found to be more sensitive to willingness to enforce than smaller operations. 본 연구는 미국 주정부의 환경정책과 축산업의 규모 및 입지 선정과의 관계에 대한 분석을 시도하였다. 분석은 업종별이 아닌 소규모, 중규모 그리고 대규모의 세 가지 규모별로 미국의 487B 주의 29년 자료를 이용한 Panel 분석을 이용하였다. 결론을 보면 일반적으로 축산엽에 대한 규제는 축산업의 구조변화에 기인한 것으로 판단된다. 산업부문으로부터 외부효과를 정부정책의 틀 안에서 내재화하기 위한 노력인 것이다. 그러나 단순히 제도의 존재 여부는 산업부문의 행위에 결정적인 영향을 주지 못하며 주정부가 규제에 대한 집행의사를 가질 때에만 영향을 줄 수 있었다. 그러나 산업부문의 급격한 구조변화가 있는 경우 주정부의 제도 존재 여부도 영향력이 있는 것으로 판단된다. 특히 축산규모에 따라 그 영향이 달랐으며 대규모 농가가 소규모 농가보다 민감하게 반응하는 것으로 나타났다.